Model Pemilihan Kendaraan Umum Dan Kendaraan Pribadi Untuk Perjalanan Bekerja Di Kota Palangka Raya: Mode Choice Public Transportation And Private Vehicle For Work In Palangka Raya City - Widjaya, Christian Dwi Putra (Media Ilmiah Teknik Sipil, 2024)
Low utility of public transport has reduced a lot of public transport passenger numbers and increased use of private modes travel for work, so public transport should be solution has turned into a burden for transportation systems increase the traffic volume due to urban. This study aims to produce models to predict the behavior mode choice valid and reliable, for design the operating model of a competitive public transport and climate policies support the existence of public transportation. To find a way for public transport back to the main mode transportation that are reliable and have a major high utility as well as to suppress the use of motorcycles and private cars. The main model has used was polynomial discrete choice mode by developing a single answer choices at Palangka Raya. The Results has received 2 different logit models. Based on logit models of type I, to up the uses public transport, can be done by pressing the ownership of private vehicles by restricting ownership 1 motorcycle and 1 car. The calculation of logit model II, increasing the use of public transport, can be done by speeding up public transport travel time and adjust travel times using private modes.